Preventive and curative activity of postharvest potassium silicate treatments to control green and blue molds on orange fruit - Moscoso-Ramírez, Pedro A.; Palou, Lluís (2017)
Preventive and curative antifungal activities of postharvest treatments with potassium silicate (PSi) against green (GM) and blue (BM) molds were evaluated on oranges (cvs. ‘Valencia’ or ‘Lanelate’) artificially inoculated in rind wounds with Penicillium digitatum and P. italicum, respectively. The most effective PSi concentration, the effect of fungal inoculum concentration, and the influence of temporal and spatial factors on antifungal activity were assessed in in vivo primary screenings. After 6 days of incubation at 20 °C, significant preventive (treatment before fungal inoculation) and curative (treatment after inoculation) activities against GM and BM were observed with PSi at 90 mM (GM and BM incidence reductions of 23 and 52 %, and 23 and 40 %, respectively). In preventive tests, the effectiveness of PSi was influenced by inoculum concentration (103, 104, 105, or 106 spores ml-1), but not by the distance between treatment and inoculation sites (10, 20 or 30 mm). PSi applied about 2 h before inoculation showed higher preventive activity than applied before 24, 48 or 96 h. In order to determine the best dip treatment conditions, PSi at 90 mM was tested at 20 or 50 °C for 60 or 150 s in small-scale trials with ‘Lanelate’ oranges artificially inoculated before or after the treatment and incubated for 7 days at 20 °C. Dips at 20 °C for 60 s were selected and subsequently applied on inoculated ‘Valencia’ oranges stored at 5 °C and 90 % RH for up to 6 weeks. Curative postharvest dips effectively reduced the incidence and severity of both GM and BM during cold storage, while preventive dips significantly reduced the severity but not the incidence. Overall, postharvest PSi treatments showed potential as a new tool to be part of non-polluting strategies to control penicillium decay of citrus fruit.